2019
DOI: 10.18860/jpips.v6i1.7811
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemanfaatan E-Learning, Lingkungan Teman Sebaya, Dan Motivasi Belajar Terhadap Prestasi Belajar

Abstract: <p><span class="fontstyle0">This study aims to examine the influence of the use of e-learning, peer group and learning motivation towards learning outcomes of Accounting in class X Accounting of SMK Hidayah Semarang. The sample of this study was students of class X Accounting SMK Hidayah Semarang with total of 41 students. A self-administered questionnaires and multiple regression analysis were used to test the research question. In addition, the results showed that there is a positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
4
0
4
Order By: Relevance
“…A prior study by Anggraeni and Sole (2018) mentioned that e-learning is linked with insufficient internet accessibility, technical skills, administration support, and inadequate content design. Additionally, Chaeuruman (2018); Pratama and Arief (2019) remarked that the existing issue of e-learning comes from the students' motivation in terms of student's willingness to be responsible for self-study. Indeed, Kaunang and Usagawa (2017) remarked that students did not have adequate experience with e-learning.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study by Anggraeni and Sole (2018) mentioned that e-learning is linked with insufficient internet accessibility, technical skills, administration support, and inadequate content design. Additionally, Chaeuruman (2018); Pratama and Arief (2019) remarked that the existing issue of e-learning comes from the students' motivation in terms of student's willingness to be responsible for self-study. Indeed, Kaunang and Usagawa (2017) remarked that students did not have adequate experience with e-learning.…”
Section: Introductionmentioning
confidence: 99%
“…Proses belajar mengajar merupakan pembentukan konsep pada materi ajar sangatlah berpengaruh, hal ini dapat mempengaruhi siswa terhadap suatu materi pembelajaran dimana dalam proses pembelajaran konsep merupakan dasar untuk berpikir dan memecahkan suatu masalah. Proses belajar mengajar pada hakikatnya adalah proses komunikasi, yaitu proses penyampaian pesan dari sumber pesan melalui saluran atau media tertentu ke penerima pesan [2]. Sebuah sumber pesan, saluran/media dan penerima pesan adalah komponen-komponen proses komunikasi.…”
Section: Pendahuluanunclassified
“…A previous study conducted by Anggraeni and Sole (2018) showed that e-learning hindrances have something to do with internet access, technical skills, inadequate teaching material designs, and administration support. Regardless of the help from the university, Pratama and Arief (2019) and Chaeruman (2018) remarked that the current e-learning issue stems from students" motivation in terms of their willingness to be accountable for their studies. Besides, other individual constraints such as personal electronic resources, the unfamiliarity of e-learning, IT mastery, and internet packages take part (Alim et al, 2019;Azhar, 2021;Fauzi & Asri, 2021;Muhajarah & Fabriar, 2020;Nisa et al, 2020;Octaberlina & Muslimin, 2020).…”
Section: Irje |Indonesian Research Journal In Education|mentioning
confidence: 99%